INTEGRATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE LANGUAGE LEARNING PROCESS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In the modern world, information and communication technologies have deeply penetrated into all spheres of human activity. It's no wonder that these technologies have found their way into education as well. The use of new information technologies expands the framework of the educational process, increases its practical orientation, and gives impetus to the development of new forms of traditional student activities. Information and communication technologies provide great opportunities for teaching the Russian language, but the question arises how to use these opportunities in the best possible way.